Luxury brands on Instagram: A netnographic approach - Aleem, A. K.; Loureiro, S. M. C. (2021 Global Fashion Marketing Conference, 2021)
The present research concerns a netnography study from June 1st 2020 to January 1st 2021on Instagram communication of six luxury brands: Louis Vuitton, Prada, Gucci, Dior, Chanel and Burberry. Five variables were taken into consideration: number of followers, number of posts, average comments, average likes and engagement rate. This qualitative study reflects the impact of digital transformation on the luxury market. Overall, results demonstrate luxury brands similarities in their Instagram communication strategy - Louis Vuitton and Gucci; Dior and Chanel; Prada and Burberry. With our findings, we were able to associate these luxury brands with the core dimensions of brand coolness. Implications of these findings are discussed with future research directions suggested.